Assistance in Processing Seaweed Cultivation into Souvenir Products of South Sulawesi Province - Srihadi, Tara Farina (SEEIJ (Social Economics and Ecology International Journal), 2022)
Indonesia is one of the largest seaweed producers in the world. Indonesia's seaweed production reached 9.12 million tons in 2021. Seaweed is one of the leading exports of Indonesian fishery products. South Sulawesi produced 3.79 million tons of seaweed in 2021, making South Sulawesi as the province in Indonesia with the largest seaweed production. Fishery resources in the Makassar Strait waters have many advantages. If the fishery resources were optimally developed, they will become a source of new economic growth for Indonesia in the future. Various products derived from processed seaweed produced by small and medium enterprises (SMEs) range from food to seaweed soap. The obstacle faced in marketing these products abroad is the regulations set by the destination country related to standardization of product quality. These constraints indicate the need for various trainings needed by SMEs craftsmen to improve the quality of products derived from processed seaweed so that they can meet the quality standard requirements in the destination country. With the development of SMEs in the seaweed cultivation sector, these enterprises can make a significant contribution to employment, income, and regional development in a sustainable manner.